2012
DOI: 10.1111/j.1740-0929.2012.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fermentation, milk production and conjugated linoleic acid in the milk of cows fed high fiber diets added with dried distillers grains with solubles

Abstract: The effects of corn dried distillers grains with solubles (DDGS) feeding on rumen fermentation and milk production in cows were evaluated using diets high in neutral detergent fiber (NDF, 45.9-46.6%). The control diet (Control) consisted mainly of hay, corn silage and concentrates. In the experimental diets, the concentrates were replaced with DDGS as 10% dry matter (DM) (10%DDGS) and 20% DM (20%DDGS). Eight cows were used for each 14-day treatment period. Effect of DDGS feeding on DM intake was not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
5
10
0
Order By: Relevance
“…This means that the HY cows likely have a better response to DMI than the LY cows, and could increase milk yield, milk protein, SNF and MUN. This finding was consistent with results reported by Kurokawa et al (2013), which showed different milk yields at similar DMI. Accordingly, the HY group showed high FCE, which would be correlated with some bacterial genera in the rumen as suggested by Jami et al (2014).…”
Section: Effect Of Dmisupporting
confidence: 94%
See 1 more Smart Citation
“…This means that the HY cows likely have a better response to DMI than the LY cows, and could increase milk yield, milk protein, SNF and MUN. This finding was consistent with results reported by Kurokawa et al (2013), which showed different milk yields at similar DMI. Accordingly, the HY group showed high FCE, which would be correlated with some bacterial genera in the rumen as suggested by Jami et al (2014).…”
Section: Effect Of Dmisupporting
confidence: 94%
“…This finding was consistent with results reported by Kurokawa et al . (), which showed different milk yields at similar DMI. Accordingly, the HY group showed high FCE, which would be correlated with some bacterial genera in the rumen as suggested by Jami et al .…”
Section: Discussionmentioning
confidence: 97%
“…Changes in milk fatty acid chain length, n-6 fatty acids and the n-3/n-6 ratio in the current experiment was altered in accordance with Gunn et al (2014) where DDGS-based diets were fed to Angus × Simmental cows. Changes in PUFA, MUFA and CLA in the current experiment are consistent with previous studies that have fed DDGS to Holsteins (Kurokawa et al, 2013) and Angus × Simmental cows (Gunn et al, 2014). SCFA and MCFAs are mainly derived from de novo synthesis in the mammary gland, whereas LCFA are derived from the diet (Bauman and Griinari, 2003).…”
Section: Milksupporting
confidence: 91%
“…The reduced total VFA concentration agrees with what has be observed in other studies when DDGS was fed to ruminants (Uwituze et al, 2011a;Kurokawa et al, 2013). The decrease in total VFA concentration mirrors the decline of DM and NDF digestibility (Table 2).…”
Section: Vfa Profilesupporting
confidence: 91%
“…However, DDGS contains more sulfur than corn, ranging from 0.3% to greater than 1% , and the high sulfur content in DDGS limits the level of DDGS that can be added to feed. It has been reported that when included at low levels in diet DDGS can be beneficial for both beef and dairy cattle (Benchaar et al, 2013;Kurokawa et al, 2013). However, when large amounts of DDGS are included in the ration of ruminant animals, rumen acidosis can result that reduces dry matter intake (DMI) and feed digestibility because DDGS contains sulfuric acid, which is used in controlling pH during ethanol fermentation and in the cleaning process of bioethanol production.…”
Section: Introductionmentioning
confidence: 99%